2017
DOI: 10.1111/cas.13286
|View full text |Cite
|
Sign up to set email alerts
|

Insulin‐like growth factor‐1 signaling is responsible for cathepsin G‐induced aggregation of breast cancer MCF‐7 cells

Abstract: Cathepsin G (CG), a neutrophil serine protease, induces cell migration and multicellular aggregation of human breast cancer MCF‐7 cells in a process that is dependent on E‐cadherin and CG enzymatic activity. While these tumor cell aggregates can cause tumor emboli that could represent intravascular growth and extravasation into the surrounding tissues, resulting in metastasis, the molecular mechanism underlying this process remains poorly characterized. In this study, we aimed to identify the signaling pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 70 publications
0
23
0
Order By: Relevance
“…Most of them were proved to be related to various cancers. For example, CTSG could promote cell migration and multicellular aggregation in human breast cancer MCF-7 cells through depending on E-cadherin 24 and was an immunotherapeutic target in acute myeloid leukemia (AML). 25 Our study showed that CTSG could inhibit OSCC proliferation, migration, invasion, and the induction of EMT in vitro, which plays a key role in tumorigenesis and progression, and a higher CTSG expression level meant well-pleasing overall survival and early-stage tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Most of them were proved to be related to various cancers. For example, CTSG could promote cell migration and multicellular aggregation in human breast cancer MCF-7 cells through depending on E-cadherin 24 and was an immunotherapeutic target in acute myeloid leukemia (AML). 25 Our study showed that CTSG could inhibit OSCC proliferation, migration, invasion, and the induction of EMT in vitro, which plays a key role in tumorigenesis and progression, and a higher CTSG expression level meant well-pleasing overall survival and early-stage tumor.…”
Section: Discussionmentioning
confidence: 99%
“…The high isoelectric points for CG (12) cause them to be easily caught in negatively charged traps such as neutrophil extracellular traps (NETs) [96]. In breast cancer, CG facilitated the E-cadherin-dependent aggregation of mammary carcinoma cells, MCF-7 [97], and it was through insulin-like growth factor-1 signaling [98]. Inhibition of CG resulted in less osteolysis in breast cancer, which indicated CG as a potential therapeutic target [99].…”
Section: Functions Of Neutrophils In the Tumor Microenvironmentmentioning
confidence: 99%
“…These four key genes are involved in various cancer-related immune processes. Cathepsin G (CTSG), an azurophil granule protease, can lead to breast cancer cell migration [ 28 , 29 ] and can enter tumor endosomes by binding to a cell surface receptor [ 30 ]. Previous studies have shown that CTSG degraded MHC I on the human glioblastoma cell surface of primary immune cells.…”
Section: Discussionmentioning
confidence: 99%